Von der Schuldenbremse zu einer ökonomisch sinnvollen Schuldenregel - Florian Schuster (Wirtschaftsdienst, 2025)
– A fiscal rule is economically sensible if it ensures sustainable public finances. The German debt brake does no such thing because it is blind to the two key determinants of fiscal sustainability - interest rates and growth. We therefore propose modelling a reformed German fiscal rule on the principles of the European fiscal rules, which relates the borrowing limit to macroeconomic conditions, in particular interest rates and growth. A dynamic fiscal rule is incompatible with rigid limits on the structural deficit in the constitution. Moreover, the new fiscal rule should tie government borrowing to productive spending, improving potential growth and debt sustainability in the long term.
Keywords: H50; H60; 330; Haushaltskonsolidierung; Reform; Deutschland; Haushaltskonsolidierung; Reform; Deutschland